On the rate of convergence of an unstable solution of a stochastic differential equation - Mynbaeva, G. U. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
We study the rate of convergence of the process ξ(tT)/T to the process w(t)/σ as T → ∞, where ξ(t) is a solution of the stochastic differential equationd ξ(t) = a(ξ(t))dt + σ(ξ(t))dw(t).